2022
DOI: 10.3390/ma15113918
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Performance of Polyurea-Reinforced Ceramic/Metal Armor Subjected to Projectile Impact

Abstract: Although polyurea has attracted extensive attention in impact mitigation due to its protective characteristics during intensive loading, the ballistic performance of polyurea-reinforced ceramic/metal armor remains unclear. In the present study, polyurea-reinforced ceramic/metal armor with different structures was designed, including three types of coating positions of the polyurea. The ballistic tests were conducted with a ballistic gun; the samples were subjected to a tungsten projectile formed into a cylinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…One of the most important applications of polyurea coatings is represented by ballistic protection [ 12 , 13 , 14 ]. This is motivated by the existence of the present conflict areas.…”
Section: Polyurea Coatings For Ballistic Protection Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important applications of polyurea coatings is represented by ballistic protection [ 12 , 13 , 14 ]. This is motivated by the existence of the present conflict areas.…”
Section: Polyurea Coatings For Ballistic Protection Applicationsmentioning
confidence: 99%
“…Figure13. Performance plotted against time for (a) normal material, (b) ideal self-healing material, and (c) self-healing material (adapted from[79,137]).…”
mentioning
confidence: 99%
“…Literature has con rmed that a H /H ratio of 2 is the optimal thickness ratio for ceramic/metal laminated composite structures 40 . Fig.…”
Section: Anti-ballistic Performance Of Two Kinds Of Composite Armor Unitmentioning
confidence: 99%
“…In addition to CBRN protection applications, ballistic protection is another field in which PU–PUR materials are valuable. PU coating could significantly increase the resistance of conventional ceramic/metal armor to create a new armor system without adding extra weight [ 47 ]. In one of our previous studies [ 48 ], we demonstrated that PU–PUR-coated aluminum plates maintained their integrity at impact with a projectile.…”
Section: Introductionmentioning
confidence: 99%